Preparation and Properties of Chitosan/Nanocrystalline Cellulose Composite Films for Food Packaging - Dong, Feng; Li, Shujun; Yan, Meiling; Li, Chunjie (Asian Journal of Chemistry, 2014)
Nanocrystalline cellulose was prepared from microcrystalline cellulose using the ultrasonication. Nanocrystalline cellulose reinforced chitosan films were prepared by solution casting. The incorporation of nanocrystalline cellulose significantly enhanced the mechanical properties.The dry and wet tensile strength of nanocomposite films were improved by 22.4 and 542 %, respectively, for the nanocomposite containing 30 wt % of nanocrystalline cellulose. The swelling behaviour was studied by analyzing the water uptake of the nanocomposite films. SEM of the nanocomposite films was found that 30 wt % of nanocrystalline cellulose was dispersed homogenously into chitosan matrix. Nanocrystalline cellulose played an important role in improving the mechanical and barrier properties of chitosan film.